2019
DOI: 10.4314/ahs.v19i1.17
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection efficacy of green synthesized gold nanoparticles for medical disinfection applications

Abstract: Background In recent times, biosyntheses of metal nanoparticles were used for several life rescue applications. In this study, Dillenia indica leaf aqueous extract was utilized for the synthesis of gold nanoparticles. Objective To test anti-microbial properties of biologically fabricated gold nanoparticles. Methods Gold nanoparticles were efficiently prepared by making use of aqueous leaf extract of Dillenia indica. The excitation of formed A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…This is of the same order of magnitude as the gold nanoparticles synthesized by the mycelium of Mucor plumbeus (i.e., 13-25 nm; average size: 17 ±4 nm, [54]). Consistent with this study, Huang et al [55] reported that the size of AuNPs fabricated by leaf aqueous extract of Dillenia indica was between 5 and 50 nm, whereas the average particle sizes of AuNPs synthesized by aqueous extract of Garcinia mangostana peel and Mentha longifolia leaf were 32.9 ± 5.3 nm and 36.4 nm, respectively [39,56]. The variation in average particle sizes could be attributed to metabolites that varied between the plants used as reducing, capping, and stabilizing agents.…”
Section: Morphological Observation-temsupporting
confidence: 90%
“…This is of the same order of magnitude as the gold nanoparticles synthesized by the mycelium of Mucor plumbeus (i.e., 13-25 nm; average size: 17 ±4 nm, [54]). Consistent with this study, Huang et al [55] reported that the size of AuNPs fabricated by leaf aqueous extract of Dillenia indica was between 5 and 50 nm, whereas the average particle sizes of AuNPs synthesized by aqueous extract of Garcinia mangostana peel and Mentha longifolia leaf were 32.9 ± 5.3 nm and 36.4 nm, respectively [39,56]. The variation in average particle sizes could be attributed to metabolites that varied between the plants used as reducing, capping, and stabilizing agents.…”
Section: Morphological Observation-temsupporting
confidence: 90%
“…In recent years, research on NP synthesis has mainly focused on green synthesis using bacteria [73,118] and plants [119][120][121][122]. For example, the marine extremophilic bacteria Pseudoalteromonas was used to obtain Au NPs with non-cytotoxic, non-genotoxic and non-oxidative stress generated over a range of concentrations but provoking alterations in DNA methylation and in the expression of DNA methyltransferase genes [118].…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…Huang et al tested the antibacterial activity of AuNPs and found that AuNPs have significant antibacterial activity against gram-negative bacteria and gram-positive bacteria, indicating that AuNPs have potential applications in the fields of medicine and biology [21]. Recently, López-Lorente et al found that spherical AuNPs have no antibacterial activity between 0 and 500 mg•L −1 , while flower-shaped AuNPs and star-shaped AuNPs of the same size have antibacterial properties at high concentrations (250~500 mg•L −1 ) [22].…”
Section: Antibacterial Effect Of Nanomaterialsmentioning
confidence: 99%